A prototype for locating and choosing office space as a service: a case of Nairobi City - Mwenda, Protasio Kithinji (Strathmore University, 2016)
Traditional work arrangements were relatively static with all the staff having a physical fixed office. This is where at some point of the day they reported to meet their supervisors, colleagues or clients. In the todays’ knowledge and collaborative economy, mobile and flexible work arrangements are the norm. That means that a good number of the staff can and indeed work from other places apart from the fixed central office. These alternative work arrangements are enabled by information and communications technology implemented in a variety of quasi-office setups with their attendant benefits and challenges. Among options available, commercial implementation of Office Space as a Service (OSaaS) has the best potential of meeting real business’ need. Unlike many other remote working arrangements, Office Space as a Service offer for hire, a formal office setup complete with required furniture, fast and secure internet connectivity, formality and privacy close to the traditional fixed office. But choosing a suitable office location, whether to hire as a service or not has been a challenge for many entrepreneurs. The choice needs to be informed by the fundamental factors that can be enablers or inhibiters of business in such a location. These include issues such as localized security and demography of the area and the actual hire/lease costs of the offices among others. Disparate information sets about OSaaS facilities has been one of the major challenges for individuals/organizations seeking to utilize these new, flexible and cost efficient office space arrangements. This research seeks to come up with an application for mapping out Office Space as a Service facilities in a given city/neighbourhood mapped against applicable localized business factors into a geo-spatial database. The application will offer an easy, quick and intuitive platform for locating and selecting available OSaaS facilities that meet a given criteria as defined by the user and a two-way communication channel between potential clients and the providers of the facilities.
A research dissertation submitted in partial fulfillment of the requirements for the Degree of Master of Science in Computer-Based Information Systems
Keywords: Prototype; Office space; Nairobi County